Liquid crystal mud film with repairing effect and preparation method thereof

The liquid crystal mud film compounded by DZ091 bionic liquid crystal and calcium octenyl starch succinate, combined with liquid crystal emulsification technology, solves the problems of traditional mud masks with poor skin feel and single efficacy, and achieves gentle and repairing care for people with sensitive skin. Effect.

CN117679328BActive Publication Date: 2025-01-24SHANDONG FREDA BIOTECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311719037.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-14
Publication Date
2025-01-24
Estimated Expiration
2043-12-14

AI Technical Summary

Technical Problem

Traditional mud films will cause tight skin during use and have a single effect, which cannot meet the needs of modern cosmetics market for gentle, repair and personalized care, especially for people with sensitive skin.

Method used

By compounding DZ091 bionic liquid crystal with calcium octenyl starch succinate, combined with liquid crystal emulsification technology, a liquid crystal mud film with improved skin feel and stable liquid crystal structure was prepared.

Benefits of technology

This liquid crystal mud mask feels better on the skin during use, is more gentle, can significantly reduce transepidermal water loss, has good repairing effects, is suitable for people with sensitive skin, and solves the problems of traditional mud masks that dry quickly and wash off. Post-tightness issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117679328B_ABST
    Figure CN117679328B_ABST
Patent Text Reader

Abstract

The present invention discloses a liquid crystal mud film with repairing effect and a preparation method thereof, wherein the liquid crystal mud film comprises an oil phase and an aqueous phase, wherein the oil phase comprises DZ091 bionic liquid crystal, calcium starch octenyl succinate and oil; and the aqueous phase comprises a moisturizer, a thickener, a powder, a preservative and water. The present invention has been verified through a large number of experimental tests: the stability of the liquid crystal structure is enhanced by compounding DZ091 bionic liquid crystal and calcium starch octenyl succinate, and the liquid crystal emulsification technology is used to make the traditional mud film feel better and gentler, and has good repairing effect, and is especially suitable for people with sensitive skin, and also solves the problem that the traditional mud film dries quickly, is tight after washing, and has a single effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cosmetics, and in particular to a liquid crystal mud film with repairing effect and a preparation method thereof. Background Art

[0002] With the influence of environmental factors such as air pollution, ultraviolet rays, seasonal changes, irregular work and rest, improper skin care, etc., the number of people with sensitive skin is increasing year by year, and consumers' awareness of sensitive skin care is increasing, which has promoted the continuous expansion of the overall sensitive skin market. In recent years, consumers with sensitive skin have gradually advanced from basic skin care demands to advanced efficacy, showing a trend of refinement and personalization.

[0003] Mud cleansing masks achieve the purpose of cleansing by removing old cuticles, enhancing the ability of the stratum corneum to regenerate, and absorbing skin secretions. In terms of the experience of use, traditional mud masks absorb a lot of oil and moisture from the skin during the drying process, which will cause the skin to feel strongly tight after washing, making it more likely to cause skin sensitivity. Therefore, traditional mud masks are not suitable for sensitive skin. In terms of efficacy, traditional mud masks are mainly for cleaning, and their efficacy is relatively single. They are no longer suitable for today's era of functional skin care. Therefore, gentle, repairing mud masks are also a demand of people with sensitive skin.

[0004] As a cutting-edge formulation technology, liquid crystal emulsification technology has obvious advantages in the field of cosmetics. Liquid crystal is an intermediate phase between "liquid" and "solid". Due to its unique double-layer structure, it can contain a large amount of bound water in the liquid crystal phase, which improves the water retention capacity of the stratum corneum. Therefore, highly moisturizing liquid crystal emulsions or creams are deeply loved by people with sensitive skin. The emulsified liquid crystal system in the cosmetics field generally belongs to lyotropic liquid crystal. Affected by factors such as temperature, type and content of liquid crystal emulsifiers, and preparation methods, the liquid crystal structure is very unstable, which limits the application of liquid crystal emulsification technology.

[0005] At present, there are few studies on the combination of liquid crystal emulsification technology and mud mask dosage forms, and there are no products on the market. Therefore, it is very necessary to develop a liquid crystal mud mask with repairing effects, suitable for sensitive skin, and with a stable liquid crystal structure. This can greatly solve the problems of poor skin feel, single dosage form, and single effect of mud mask products. Summary of the invention

[0006] In view of the above problems, the present invention provides a liquid crystal mud mask with repairing effect and a preparation method thereof. The present invention has confirmed through a large number of experimental tests: the stability of the liquid crystal structure is enhanced by compounding DZ091 bionic liquid crystal and calcium starch octenylsuccinate. The mud mask prepared by liquid crystal emulsification technology has a better skin feel and is gentler than traditional mud masks, and has good repairing effect. It is especially suitable for people with sensitive skin, and also solves the problems of traditional mud masks that dry quickly, feel tight after washing, and have a single effect.

[0007] In order to achieve the above technical objectives, the technical solution provided by the present invention is as follows: a liquid crystal mud film with repairing effect, comprising an oil phase and a water phase, characterized in that the oil phase comprises the following components: DZ091 bionic liquid crystal, calcium octenyl succinate starch and oil; the water phase comprises the following components: a moisturizer, a thickener, a powder, a preservative and water.

[0008] Furthermore, the aqueous phase may also include other auxiliary materials such as skin conditioners.

[0009] Among them, DZ091 bionic liquid crystal plays the role of emulsifier, purchased from Shanghai Zhina Biotechnology Co., Ltd., with the trade name DZ091 bionic liquid crystal. The raw material is composed of cetearyl alcohol>50%, phytosterols 10%-20%, glyceryl isostearate 10%-20%, and hydrogenated lecithin 1%-5%. Calcium starch octenylsuccinate was purchased from Ingredion Food Ingredients Co., Ltd. with the trade name FARMAl TM AF1100.

[0010] Furthermore, the mass percentages of the components of the above-mentioned liquid crystal mud film are: DZ091 bionic liquid crystal 2.0% to 5.0%, calcium starch octenylsuccinate 0.5% to 2.0%, oil 2% to 20%, moisturizer 2% to 15%, thickener 0.2% to 1.2%, powder 5% to 15%, preservative 0.4% to 2%, other auxiliary materials 0 to 18%, and the balance is water.

[0011] Further preferably, the mass percentages of the components of the above-mentioned liquid crystal mud film are: DZ091 bionic liquid crystal 2.5% to 3.5%, calcium starch octenylsuccinate 1.0% to 1.5%, oil 5% to 15%, moisturizer 6% to 10%, thickener 0.3% to 1.0%, powder 10% to 15%, preservative 0.4% to 1%, other auxiliary materials 0 to 9%, and the balance is water.

[0012] Furthermore, the moisturizer includes but is not limited to one or more of glycerin, dipropylene glycol, butylene glycol, propylene glycol, methylpropanediol, and 1,2-hexanediol; the thickener includes but is not limited to sodium polyacrylate, sodium polyacrylate grafted starch, carbomer, xanthan gum, hydroxyethyl cellulose, polyacrylate cross-linked polymer-6, ammonium acryloyldimethyltaurate / VP copolymer, hydroxyethyl acrylate / sodium acryloyldimethyltaurate copolymer, SEPIPLUS 400 (purchased from Seppic), SIMULEGEL EG (purchased from Seppic), and magnesium aluminum silicate; the powder includes but is not limited to any one or more of kaolin, bentonite, diatomaceous earth, titanium dioxide, and carbon powder; the preservative is any one or more of hydroxyacetophenone, caprylhydroxamic acid, and phenoxyethanol.

[0013] Further, the oil acts as an emollient, including but not limited to cetearyl alcohol, isononyl isononanoate, squalane, caprylic / capric triglyceride, beeswax, mineral oil, walnut seed oil, meadowfoam seed oil, polydimethylsiloxane, cyclopentasiloxane, isododecane, jojoba seed oil, triethylhexanoin, behenyl alcohol, shea butter, pentaerythrityl tetraisostearate, dicaprylyl carbonate, and tocopheryl acetate, or a combination of two or more thereof.

[0014] The present invention also provides a method for preparing the above liquid crystal mud film, which is characterized in that it specifically comprises the following steps:

[0015] S1 aqueous phase preparation:

[0016] Add the thickener into water and stir to disperse until there are no particles, then add the powder raw material and stir to disperse until there are no particles, then add the moisturizer and heat to 80-85°C;

[0017] S2 oil phase preparation:

[0018] Heat the oil to 80-85℃ to melt it, then add DZ091 bionic liquid crystal and calcium octenyl succinate starch to melt and disperse;

[0019] S3 Homogenization:

[0020] The water phase and the oil phase are mixed homogeneously, and when the temperature drops to 40-50°C, other auxiliary materials such as preservatives are added, and the mixture is stirred and mixed evenly to prepare a liquid crystal mud film.

[0021] Furthermore, the homogenization speed of step S3 is 3000 rpm to 8000 rpm, and the homogenization time is 4 to 6 minutes.

[0022] The beneficial technical effects of the present invention are:

[0023] 1. The liquid crystal mud film prepared by the present invention is compounded with DZ091 bionic liquid crystal and calcium starch octenyl succinate to improve the stability of the mud film and the liquid crystal structure.

[0024] 2. The mud mask prepared by the liquid crystal emulsification technology of the present invention is more friendly to sensitive skin and has a better skin feel; by compounding DZ091 bionic liquid crystal with calcium starch octenyl succinate, the TEWL value can be significantly reduced when using D14 and D28, and has a good repair effect;

[0025] 3. The liquid crystal mud mask prepared by liquid crystal emulsification technology solves the problem of traditional mud masks drying quickly and feeling tight after washing. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : The morphology of the sample under polarized light of Example 1;

[0027] Figure 2 : The morphology of the sample under polarized light of Example 2;

[0028] Figure 3 : The morphology of the sample of Example 2 after one month of hot and cold cycling under polarized light;

[0029] Figure 4 : The morphology of the sample under polarized light of Example 3;

[0030] Figure 5 : The morphology of the sample of Example 4 under polarized light;

[0031] Figure 6 : The morphology of the sample of Comparative Example 1 under polarized light;

[0032] Figure 7 : The morphology of the sample of Comparative Example 2 under polarized light;

[0033] Figure 8 : Morphology of the sample of Comparative Example 2 under polarized light after one month of hot and cold cycling. DETAILED DESCRIPTION

[0034] The present invention is further described below by examples and drawings, but the present invention is not limited to the scope of the embodiments. Based on the embodiments in the present invention, any variation of the present invention by those skilled in the art without making a creative premise belongs to the protection scope of the present invention. Meanwhile, in the embodiments of the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0035] Table 1 Formulations of liquid crystal mud films of Examples 1 to 4 and Comparative Examples 1 to 4

[0036]

[0037]

[0038] The above-mentioned GRANPOWDER USQ is purchased from Grant Industries, Inc., INCI name: polydimethylsilsesquioxane (60%), HDI / trimethylol hexyl lactone crosspolymer (40%); SSE-20 trade name Glucamate TM SSE-20 emulsifier is purchased from Lubrizol, INCI name: PEG-20 methyl glucose sesquistearate (99.975%), tocopherol (vitamin E) (0.025%); SS trade name is GLUCATE(TM) SS EMULSIFIER, 41G FBR DR, purchased from Lubrizol, INCI name: methyl glucose sesquistearate.

[0039] The preparation method of the mud film samples described in Examples 1 to 4 and Comparative Examples 1 to 4 comprises the following steps:

[0040] S1 aqueous phase preparation:

[0041] Add thickeners (xanthan gum, magnesium aluminum silicate and SEPIPLUS 400) into water and stir to disperse until there are no particles, then add powder raw materials and stir to disperse until there are no particles, then add moisturizers (dipropylene glycol and glycerin) and heat to 80-85°C;

[0042] S2 oil phase preparation:

[0043] Heat the oil to 80-85°C to melt, then add DZ091 bionic liquid crystal and calcium octenyl succinate starch (the raw materials used in the comparative example are shown in Table 1) to melt and disperse;

[0044] S3 Homogenization:

[0045] The water phase and the oil phase were mixed and homogenized at a homogenization speed of 5000 rpm for 5 minutes, and the temperature was lowered to 45°C. The preservative was added and stirred and mixed evenly to prepare a liquid crystal mud film.

[0046] Test Example 1: Stability Test

[0047] The samples of Examples 1 to 4 and Comparative Examples 1 to 4 were placed at room temperature, -18°C, 4°C, 45°C, and subjected to cold and hot cycles (-18°C, 4°C, 45°C, cycled once every 3 days) for corresponding periods of time for stability observation, and the stability of the product was judged by whether oil discharge, water discharge, coarsening of the material body, and the like occurred. If unstable phenomena such as oil discharge, water discharge, coarsening of the material body, etc. did not occur, the stability passed, and the reason for failure was indicated. The specific results are shown in Table 2 below.

[0048] Table 2 Stability test results

[0049]

[0050] As shown in Table 2, in Examples 1 to 4, DZ091 bionic liquid crystal and calcium starch octenyl succinate were compounded in different proportions, and the stability results were good; in Comparative Example 1, only DZ091 bionic liquid crystal was used, and the material body became coarse at low temperature; in Comparative Example 2, DZ091 bionic liquid crystal was compounded with USQ, and the material body became coarse at low temperature; in Comparative Example 3, SS and SSE-20 emulsifiers were used to compound calcium starch octenyl succinate to prepare a non-liquid crystal structure mud film, and the material body became coarse at low temperature and in circulation; in Comparative Example 4, only calcium starch octenyl succinate was used to prepare the mud film, and the water and oil output were unstable at room temperature, low temperature, high temperature, and circulation. Therefore, the liquid crystal mud film prepared by compounding DZ091 bionic liquid crystal and calcium starch octenyl succinate can improve the stability of the mud film.

[0051] Test Example 2: Liquid crystal structure stability test

[0052] The prepared samples of Examples 1 to 4 and Comparative Examples 1 to 2 were photographed under a polarizing microscope. Comparative Example 3 was a non-liquid crystal mud film, and no liquid crystal structure was observed under a polarizing microscope, so it was not photographed. Comparative Example 4 did not pass the stability test, so it was not photographed. The polarizing microscope morphology of Examples 1 to 4 and Comparative Examples 1 to 2 is shown in detail. Figure 1 , Figure 2 , Figures 4 to 7 .

[0053] The samples of Examples 1 to 4 and Comparative Examples 1 to 2 in Test Example 1 were placed at room temperature, -18°C, 4°C, and 45°C and the liquid crystal structure was photographed regularly to record the changes in the liquid crystal structure. The results are shown in Table 3. The morphology under polarized light of Example 2 and Comparative Example 2 after one month of hot and cold cycles is shown in Table 3. Figure 3 , Figure 8 .

[0054] Table 3 Liquid crystal structure stability test results

[0055]

[0056] Depend on Figures 1 to 8 As shown in Table 3, the liquid crystal structures of Examples 1 to 4 are significantly more than those of Comparative Examples 1 to 2, and the stability of the liquid crystal structures is good. The liquid crystal structures of Comparative Examples 1 to 2 are less, and the high temperature and cycle stability are poor. The liquid crystal structures of Examples 2 and 3 are small, uniform in size, and better in morphology. The liquid crystal structures of Examples 1 and 4 are larger, with large size differences and slightly poorer stability. This indicates that the liquid crystal mud film prepared by compounding bionic liquid crystal with calcium starch octenyl succinate can increase the number of liquid crystal structures and improve the stability of the liquid crystal structure, but the compounding ratio of bionic liquid crystal and calcium starch octenyl succinate will also affect the morphology and stability of the liquid crystal.

[0057] Test Example 3: Skin feel test

[0058] Questionnaire (A total of 28 people were selected for this questionnaire, aged 23 to 50 years old, both male and female).

[0059] The experiment recruited 28 subjects, and Examples 1 to 4 and Comparative Examples 1 to 3, which passed the stability at room temperature, were used as test samples. The sample of Comparative Example 4 could not be tested due to water and oil release at room temperature. The same sample was tried by 4 volunteers, and the product was tried on the face respectively. Each time, 4 grams of sample was accurately weighed, evenly applied to the face, and washed with clean water after 30 minutes. Based on the four indicators of drying speed, moisturizing degree, smearing feeling, and no discomfort as evaluation criteria, Examples 1 to 4 and Comparative Examples 1 to 3 were scored: 1-5 points. The higher the score, the more popular the sample is among the volunteers and the better the performance is. Detailed results are shown in Table 4.

[0060] Table 4 Skin feel test results

[0061]

[0062]

[0063] As shown in Table 4, by comparing Examples 1 to 4 and Comparative Examples 1 to 3, the overall satisfaction is Example 2> Example 3> Example 1> Example 4> Comparative Example 2> Comparative Example 1> Comparative Example 3, and there is little difference in the overall satisfaction between Example 2 and Example 3. The skin feel of the liquid crystal mud film prepared by compounding DZ091 bionic liquid crystal and calcium starch octenyl succinate in Examples 1 to 4 is better than that of the liquid crystal mud film prepared by using DZ091 bionic liquid crystal alone in Comparative Example 1, the liquid crystal mud film prepared by using DZ091 bionic liquid crystal and USQ in Comparative Example 2, and the non-liquid crystal mud film in Comparative Example 3.

[0064] Test Example 4: Irritation Evaluation Test

[0065] The experiment recruited 30 subjects, both male and female, aged 23 to 50 years old, and used Examples 1 to 4 and Comparative Examples 1 to 3 that passed the stability test at room temperature as the test substances, and the blank as the negative control. The test method was to select an area not exceeding 50 mm 2 , a suitable spot tester with a depth of about 1mm, and about 0.020-0.025g of the test substance is added to the spot tester by a closed patch test method. A hypoallergenic tape is applied to the back of the test subject. Each tester tests eight samples of the blank group, Examples 1-4, and Comparative Examples 1-3. The test substance is removed after 24 hours, and the skin reaction is observed at 0.5, 24, and 48 hours after removal. The results are recorded according to the skin reaction grading standard (Table 5) in the "Cosmetic Safety Technical Specifications 2015". The detailed results are shown in Table 6.

[0066] Table 5 Skin reaction grading standards

[0067]

[0068] Table 6 Irritation evaluation test results

[0069]

[0070]

[0071] As shown in Table 6, the samples of Examples 1 to 4 had no adverse reactions and were mild and non-irritating; Comparative Examples 1 to 3 all had adverse reactions to varying degrees, among which the non-liquid crystal mud film comparative example 3 had the most severe adverse reactions. This indicates that the liquid crystal mud film prepared from DZ091 bionic liquid crystal and calcium starch octenyl succinate is milder and reduces the irritation of the mud film.

[0072] Test Example 5: Human body repair efficacy evaluation experiment

[0073] The experiment recruited 30 subjects who were positive for the lactic acid sting test, regardless of gender, aged between 18 and 50 years old, and evaluated the human body repair efficacy of Example 2 and Comparative Example 3. Example 2 was applied to the left face of the subject, and Comparative Example 3 was applied to the right face of the subject. It was used twice a week, and each sample was used about 2g each time. It was used continuously for 4 weeks to evaluate the transepidermal water loss TEWL value (Tewameter TM300). The test period was before use (D0), after 2 weeks of use (D14), and after 4 weeks of use (D28). Under the test conditions, the higher the TEWL value obtained, the more transepidermal water loss per unit time and unit cross-sectional area; the lower the TEWL value, the less transepidermal water loss per unit time and unit cross-sectional area. The detailed results are shown in Table 7.

[0074] Table 7 Transepidermal water loss TEWL value and statistical results of the face

[0075]

[0076] Note: ① Normality test P value>0.05, indicating that the data obeys normal distribution, and paired t test is used. If it does not obey normal distribution, non-parametric test is used; ② Significant P value<0.05, indicating that there is a significant difference compared with before use, indicated by "*"; P value<0.01, indicated by "**"; P value<0.001, indicated by "***". Significant P value≥0.05, indicating that there is no significant difference compared with before use, indicated by "-".

[0077] As shown in Table 7, the liquid crystal mud film prepared from DZ091 bionic liquid crystal and calcium starch octenyl succinate in Example 2 can significantly reduce the TEWL value when used at D14 and D28, and has a significant repair effect; the non-liquid crystal mud film in Comparative Example 3 has no significant effect on reducing TEWL when used at D14 and D28, and has no repair effect. Therefore, the liquid crystal mud film prepared from DZ091 bionic liquid crystal and calcium starch octenyl succinate has a good repair effect.

Claims

1. A liquid crystal mud film with repairing effect, characterized in that: The components and mass percentages of the liquid crystal mud film are: DZ091 bionic liquid crystal 2.5% to 3.5%, octenyl succinate starch calcium 1.0% to 1.5%, oil 5% to 15%, moisturizer 6% to 10%, thickener 0.3% to 1.0%, powder 10% to 15%, preservative 0.4% to 1%, other auxiliary materials 0 to 9%, and the balance is water; The DZ091 bionic liquid crystal is composed of cetearyl alcohol>50%, phytosterols 10%-20%, glyceryl isostearate 10%-20%, and hydrogenated lecithin 1%-5%.

2. The liquid crystal mud film according to claim 1, characterized in that: The moisturizing agent is one or a combination of glycerin, dipropylene glycol, butylene glycol, propylene glycol, methyl propanediol, and 1,2-hexanediol.

3. The liquid crystal mud film according to claim 1, characterized in that: The thickener is any one of sodium polyacrylate, sodium polyacrylate grafted starch, carbomer, xanthan gum, hydroxyethyl cellulose, polyacrylate cross-linked polymer-6, ammonium acryloyldimethyltaurate / VP copolymer, hydroxyethyl acrylate / sodium acryloyldimethyltaurate copolymer, SEPIPLUS 400, SIMULEGELEG, and magnesium aluminum silicate, or a combination of more than one of the above.

4. The liquid crystal mud film according to claim 1, characterized in that: The powder is any one or a combination of kaolin, bentonite, diatomaceous earth, titanium dioxide, and carbon powder; the preservative is any one or a combination of hydroxyacetophenone, caprylhydroxamic acid, and phenoxyethanol.

5. The liquid crystal mud film according to claim 1, characterized in that: The oil is any one of cetearyl alcohol, isononyl isononanoate, squalane, caprylic / capric triglyceride, beeswax, mineral oil, walnut seed oil, meadowfoam seed oil, polydimethylsiloxane, cyclopentasiloxane, isododecane, jojoba seed oil, triethylhexanoin, behenyl alcohol, shea butter, pentaerythrityl tetraisostearate, dicaprylyl carbonate, and tocopheryl acetate, or a combination of two or more thereof.

6. The method for preparing a liquid crystal mud film according to claim 1, characterized in that: The specific steps include: S1 aqueous phase preparation: Add the thickener into water and stir to disperse until there are no particles, then add the powder raw material and stir to disperse until there are no particles, then add the moisturizer and heat to 80-85°C; S2 oil phase preparation: Heat the oil to 80-85℃ to melt it, then add DZ091 bionic liquid crystal and calcium octenyl succinate starch to melt and disperse; S3 Homogenization: The water phase and the oil phase are mixed homogeneously, and when the temperature drops to 40-50° C., preservatives and other auxiliary materials are added, and the mixture is stirred and mixed uniformly to prepare a liquid crystal mud film.

7. The method for preparing a liquid crystal mud film according to claim 6, characterized in that: The homogenization speed of step S3 is 3000 rpm to 8000 rpm, and the homogenization time is 4 to 6 minutes.

Citation Information

Patent Citations

  • Bionic liquid crystal composition as well as preparation method and application thereof

    CN117122523A